The significance of presenteeism for the value of lost production: the case of rheumatoid arthritis - Rikke Søgaard; Jan Sørensen; Louise Linde; et al (Dove Medical Press, 2010)
Rikke Søgaard1, Jan Sørensen1, Louise Linde2, Merete L Hetland2,31CAST – Centre for Applied Health Services Research and Technology Assessment, University of Southern Denmark, Denmark; 2Department of Rheumatology, Hvidovre and Glostrup Hospitals, Denmark; 3The DANBIO registry, Hvidovre and Glostrup Hospitals, DenmarkAbstract: Lost production can be due to individuals’ time lost to work (absenteeism), as well as their time at work with reduced productivity because of ill health (presenteeism). A sound methodological framework for the assessment of presenteeism remains to be established but given its significance, ignoring it would lead to severe underestimations, eg, in cost-of-illness studies. The objective of this study was to assess the empirical significance of absenteeism and presenteeism in terms of production loss using the case of rheumatoid arthritis (RA). Selected modules from the Health and Labor Questionnaire were applied in a cross-sectional study of 3,704 patients with RA. The costs of absenteeism and presenteeism were estimated using the Human Capital approach, and the impact of including multipliers adjusting for the productivity effect of a workers’ absence or impaired presenteeism on societal productivity was demonstrated. RA-related absenteeism over the last 14 days was 22.31 hours (standard deviation [SD], 26.51) with a resulting cost of €473 (SD, 575) and €762 (SD, 926) depending on whether a multiplier was included. Presenteeism was found to affect 7.98 (SD, 3.24) working days over the last 14 days with a resulting cost of €168 (SD, 203) and €203 (SD, 245), again depending on whether a multiplier was included. Overall, this article demonstrates that the value of lost production due to RA could be subject to an almost factor 2 increase if productivity effects of presenteeism and general multipliers are included.Keywords: work limitations, Health and Labor Questionnaire, productivity, production loss